2017
DOI: 10.1021/acs.langmuir.7b02669
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Studies of the Diffusion of Intrinsic Defects and Silicon Dopants in Bulk InAs

Abstract: We expose the predominant diffusional pathways for In and As in InAs, as well as dopant Si atoms in InAs, using Nudged Elastic Band calculations in conjunction with accurate Density Functional Theory calculations of the energy of defective systems. Our results show that As is a very fast diffuser compared to In and Si for both vacancy-assisted and interstitially mediated mechanisms. Larger indium atoms, on the other hand, are very slow diffusers and strongly prefer to remain on the In sublattice. Silicon also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…When one vacancy is generated on an In atom site, one As atom on a nearest-neighbor site might dissociate from the host and fill up this vacancy site, forming the V As As In complex. Here, we will not consider the As counterpart of V In In As , since a previous study has already reported that the defect complex of V In In As is unstable and spontaneously relaxes back to V As single vacancy-type defect [26].…”
Section: Formation Energy Of Vacanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…When one vacancy is generated on an In atom site, one As atom on a nearest-neighbor site might dissociate from the host and fill up this vacancy site, forming the V As As In complex. Here, we will not consider the As counterpart of V In In As , since a previous study has already reported that the defect complex of V In In As is unstable and spontaneously relaxes back to V As single vacancy-type defect [26].…”
Section: Formation Energy Of Vacanciesmentioning
confidence: 99%
“…A 3 × 3 × 3 supercell with 108 In and 108 As atoms and referenced for defect calculations is illustrated in Figure 1b. Our study aims to provide an extensive and accurate study of the intrinsic point defect formation which is missed in the literature, e.g., a very recent computational study [26], but is highly desirable. Here, the small yellow ball denotes As atoms, while the large silver balls are for In atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In a binary alloy such as GaAs, the addition of a third element to form a ternary compound may modify the incorporation of dopant species via one or more mechanisms. First, the third element (Al in this case) may change the bulk defect formation energy associated with dopant substitution by virtue of differences in size or bonding, which could increase or decrease the dopant incorporation rate. Second, an additional group III element such as In or Al will compete for binding sites, which could decrease the dopant incorporation rate.…”
mentioning
confidence: 99%